FAKTOR-FAKTOR YANG MEMPENGARUHI KEPEMILIKAN MANAGERIAL - DEA IMANTA; RUTJI SATWIKO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
The purpose of this research is to provide empirical evident whether debt policy, dividend policy, institutional ownership, business risk, firm size, earning volatility, profitability and company value have significant influence to managerial ownership. This research used data were taken from all companies listed in Indonesia Stock Exchange over the three years period 2006 till 2008. This research used purposive sampling method. The sample of this research consists of 30 companies that meet the criteria. This research uses multiple regresion method to see the contribution of each variable in influance managerial owner-ship. The empirical result indicates that only institutional ownership has significant influence to managerial ownership, while other variables do not have significant influence to mangerial ownership.